2004
DOI: 10.1016/s0899-3467(07)60086-x
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Windmill Pitch: Biomechanics and Injuries

Abstract: (J Chiropr Med 2004;3:53-62)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The primary aim of our study was to assess the characteristics of softball pitchers' upper and lower extremity ROM and strength and compare these characteristics across level of competition. To our knowledge, this is the first study to compare high school and collegiate athletes across levels of play and to examine hip extension and hip and shoulder flexion ROM . Ultimately, our objective is to contribute to a better understanding of expected joint health among female softball pitchers.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The primary aim of our study was to assess the characteristics of softball pitchers' upper and lower extremity ROM and strength and compare these characteristics across level of competition. To our knowledge, this is the first study to compare high school and collegiate athletes across levels of play and to examine hip extension and hip and shoulder flexion ROM . Ultimately, our objective is to contribute to a better understanding of expected joint health among female softball pitchers.…”
Section: Discussionmentioning
confidence: 98%
“…We found that shoulder IR strength was greater in the throwing arm. During the delivery phase of the windmill pitch, the shoulder of the throwing arm internally rotates rapidly . This repeated motion may contribute to the increased IR strength of the throwing arm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the majority of studies have focused on shoulder musculature and function—specifically the deltoid muscle, rotator cuff musculature, the pectoralis major, the serratus anterior, the biceps brachii muscle, the latissimus dorsi, and the triceps muscle. 2 , 4 While these studies have provided insight into the shoulder musculature during windmill pitching, there have not been any studies evaluating the musculature of the forearm. 2 , 5 , 6 Argo et al 1 published a series of elbow injuries and surgeries in female athletes.…”
mentioning
confidence: 99%